Design and implementation of a Moodle-based adaptive hypermedia system for Indonesian vocabulary learning and character education - Sari, Rafika Muspita; Nasution, Atikah Rahmah; Ifriqia, Fartika; Sutikno, Sutikno; Asnawi, Asnawi; Kartolo, Rahmat; Herman, Herman; Al-Awawdeh, Nabil (Research Journal in Advanced Humanities, 2026)
This study explores the implementation of a Moodle-based adaptive hypermedia system to enhance Indonesian vocabulary comprehension and support character development among senior high school (SMA) students. The research employed a qualitative approach, collecting data through observations, student assessments via Google Forms, and reflective notes from classroom interactions. The study focused on how adaptive learning strategies, multimedia resources, and personalized learning pathways influence students’ understanding of vocabulary and their self-directed learning behaviors. The results indicate that the Moodle-based adaptive hypermedia system significantly improved students’ vocabulary mastery, with average scores increasing from 61.5% in the initial assessment to 84% in the final assessment. Additionally, students exhibited greater responsibility, discipline, and engagement throughout the learning process. The system’s adaptive features, combined with multimedia support and interactive tasks, provided individualized learning experiences that accommodated diverse learning needs. Observations also highlighted the positive impact of the system on collaborative learning, as students actively assisted each other in understanding vocabulary items. The study contributes to both educational theory and practice by demonstrating the benefits of adaptive e-learning environments in enhancing language proficiency and promoting self-regulated learning among secondary school students.